2014
DOI: 10.1111/bph.12832
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of NO in biological samples

Abstract: Although the physiological regulatory function of the gasotransmitter NO (a diatomic free radical) was discovered decades ago, NO is still in the frontline research in biomedicine. NO has been implicated in a variety of physiological and pathological processes; therefore, pharmacological modulation of NO levels in various tissues may have significant therapeutic value. NO is generated by NOS in most of cell types and by non-enzymatic reactions. Measurement of NO is technically difficult due to its rapid chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 131 publications
4
75
0
2
Order By: Relevance
“…Analysis of NO content was performed with double integration of the NO signal as described previously [34][35][36]. NO content of the samples were expressed in arbitrary units as this method enables a semi-quantitative assessment of NO content in biological samples (see for review Csonka et al [37]). …”
Section: Antibodies and Materialsmentioning
confidence: 99%
“…Analysis of NO content was performed with double integration of the NO signal as described previously [34][35][36]. NO content of the samples were expressed in arbitrary units as this method enables a semi-quantitative assessment of NO content in biological samples (see for review Csonka et al [37]). …”
Section: Antibodies and Materialsmentioning
confidence: 99%
“…Hepatocytes produce NO in picomolar levels (6), therefore it is difficult to detect and quantify NO levels within them. In the present study, the HPLC-fluorescence detector method was employed.…”
Section: Discusionmentioning
confidence: 99%
“…The Griess reaction is inexpensive, simple and fast; however, the limit of detection is ~0.5 µM, which restricts the application of this colorimetric method for quantifying micromolar, nanomolar and picomolar levels of NO 2 -, and therefore physiological amounts (6). Furthermore, the media composition in biological systems may alter the measurements of NO due to the presence of other proteins, such as hemoglobin, which is also detected at 540 nm (7).…”
Section: Introductionmentioning
confidence: 99%
“…Its importance for biomedical research is owing to: (a) it is a free radical found in all tissues, (b) it is involved in a large number of physiological and pathological processes, (c) NO donors are used in clinical therapy and new molecules with the ability to release NO are under constant demand (1). NO concentrations are particularly important since, as with any messenger molecule, too little or too much of the substance can result in pathological events (2,3).…”
Section: Introductionmentioning
confidence: 99%